Thermoplastic Vulcanizate Based on Poly(lactic acid) and Acrylic Rubber Blended with Ethylene Ionomer - Kittisak Jantanasakulwong (2018)
© 2016 Taylor & Francis Group, LLC. A new thermoplastic vulcanizate (TPV) was developed by meltblending of poly(lactic acid) (PLA), acrylic rubber (ACM), and ethylene-methacrylic acid with sodium ions (EMAA-Na). The PLA/ACM/EMAA-Na blend showed low-yield strength, low modulus, and excellent strain recovery. It also demonstrated an increase in complex viscosity and decrease in melting temperature due to the interfacial reaction between the PLA and the ACM phases. The Fourier transform infrared spectroscopy results indicate that EMAA-Na can interact with both PLA and ACM, and that the Na+ions act as a catalyst for the interfacial reaction between PLA and ACM, while PLA does not react with ACM without EMAA-Na. Moreover, the tensile strength at break of the PLA/ACM/EMAA-Na blend was observed to be extremely improved by the addition of hexamethylenediaminecarbamate (HMDC) due to the increasing of the cross-link density inside the rubber phase. The morphology of the PLA/ACM/EMAA-Na blend with HMDC was finer than that of PLA/ACM/EMAA-Na without HMDC. From the results, it is suggested that the interfacial reaction between the PLA and the ACM phases, the cross-linking in the ACM phase, and the finer morphology improved the mechanical properties of the blend.